Antibiotic tolerance in biofilm persister cells of Staphylococcus aureus and expression of toxin-antitoxin system genes. (October 2021) - Karimaei, Samira; Kazem Aghamir, Seyed Mohammad; Foroushani, Abbas Rahimi; Pourmand, Mohammad Reza
Abstract: The ability of Staphylococcus aureus to form biofilm and persister cells is the main cause of recurrent infections. This study aimed to evaluate the expression of toxin-antitoxin (TA) systems in persister cells within S. aureus biofilms. Time-dependent variation in the persister population present in biofilms of S. aureus was examined after treatment with bactericidal antibiotics. Then, the relative expression level of type II TA system ( mazF, relE1, and relE2 ), type I TA system ( sprG ), and clpP protease genes in S. aureus strains were assessed by Real _Time PCR. Among the sixteen isolates, two isolates were found to be the strongest biofilm producers. The established biofilm of these isolates showed a comparable biphasic pattern at the lethal dose of the antibiotics. The expression level of TA system genes was increased and strain-specific expression patterns were observed under antibiotics stress conditions. Persisters within a biofilm may establish a reservoir for relapsing infection and could contribute to treatment failures. Hence, the possible role of the TA systems should be considered in biofilm and persister cell formation. Highlights: The ability of S. aureus to biofilm production and persister cells formation is the main cause of recurrent infections. Persister cells are a small subpopulation of bacteria that indicate resistance to antibiotics without genetic alteration. Persister cells make a part of the heterogeneous population of the biofilm which can tolerate antibiotics. Persisters within a biofilm may establish a reservoir for relapsing infection and could contribute to treatment failures.